Sharq va Gʻarb falsafasining insoniyat tafakkuri taraqqiyotida tutgan oʻrni - Quvondiqova Sohiba Orif qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article covers the essence and main tasks of philosophy. Philosophy is based on an in-depth analysis of human thinking and studies such fundamental concepts as existence, knowledge, truth, morality and society. The article also analyzes the specific aspects of Eastern and Western philosophy and considers their contribution to human thinking. Western philosophy is distinguished by its emphasis on analytical thinking and scientific methods, while Eastern philosophy emphasizes spirituality and inner harmony as the main value. This article is aimed at understanding the importance of philosophy in human life and reveals the topic in depth through historical examples and philosophical currents.